2020
DOI: 10.2174/1871527319666200117110056
|View full text |Cite
|
Sign up to set email alerts
|

BDNF-TrkB and proBDNF-p75NTR/Sortilin Signaling Pathways are Involved in Mitochondria-Mediated Neuronal Apoptosis in Dorsal Root Ganglia after Sciatic Nerve Transection

Abstract: Background: Brain-Derived Neurotrophic Factor (BDNF) plays critical roles during development of the central and peripheral nervous systems, as well as in neuronal survival after injury. Although proBDNF induces neuronal apoptosis after injury in vivo, whether it can also act as a death factor in vitro and in vivo under physiological conditions and after nerve injury, as well as its mechanism of inducing apoptosis, is still unclear. Objective: In this study, we investigated the mechanisms by which proBDNF cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Kim et al 151 Inhibiting mPTP opening in PNI with cyclosporin A attenuates allodynia and spinal cord cytochrome c release. Wang et al 150 Pro-BDNF induces mitochondria-mediated apoptosis of neurons and satellite glia in vitro Diabetic neuropathy…”
Section: Peripheral Nerve Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 151 Inhibiting mPTP opening in PNI with cyclosporin A attenuates allodynia and spinal cord cytochrome c release. Wang et al 150 Pro-BDNF induces mitochondria-mediated apoptosis of neurons and satellite glia in vitro Diabetic neuropathy…”
Section: Peripheral Nerve Injurymentioning
confidence: 99%
“…149 Mitochondrial dysfunctions can trigger apoptosis and axonal degeneration in the periphery and spinal cord, leading to pain. [149][150][151][152] However, neuropathic pain in PNI is not exclusively caused by degeneration. Both peripheral and central sensitization contribute to pain maintenance.…”
Section: Mitochondria In Pnimentioning
confidence: 99%
“…Under physiological conditions, proBDNF induces neuronal apoptosis in vitro and in vivo after nerve injury [ 33 , 34 ]. In the present study, our data indicated that the survival rate of prefrontal cortical or hippocampal neurons treated with recombinant p75NTR and siJNK was significantly higher than that in the PSD group.…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al (2018) found that GOLPH3 regulation sensitizes glioma cells to apoptotic stimuli induced by the chemotherapy drug temozolomide. The p75 neurotrophin receptor (p75NTR) is a glycoprotein belonging to the TNFR/nerve growth factor receptor family that is traditionally detected at the cell membrane (Wang et al, 2020). Recently, Giraud et al (2011) found, using immunofluorescence microscopy, that a part of p75NTR is located in the GA of glioma cells.…”
Section: Gliomamentioning
confidence: 99%